Ultrasonographic evaluation of adrenal glands in clinically healthy Korean raccoon dogs (Nyctereutes procyonoides koreensis) - Park, Jinkyung; Kim, Myeongsu; Han, Jae-Ik; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2025)
IntroductionUltrasonographic evaluation of the adrenal glands is a valuable tool for detecting structural abnormalities during clinical assessment. However, no species-specific sonographic reference values have been established for Korean raccoon dogs (Nyctereutes procyonoides koreensis), limiting the application of this modality in clinical and wildlife settings.MethodsSagittal ultrasonographic images from 38 clinically healthy Korean raccoon dogs were retrospectively analyzed. Adrenal length and cranial and caudal pole heights were measured bilaterally, with each parameter obtained three times per gland and the median value used for analysis. Gland morphology and corticomedullary distinction were visually assessed, and statistical tests were performed to evaluate differences by sex, body weight, and laterality.ResultsAll adrenal glands were clearly visualized without sedation and consistently exhibited a peanut-shaped morphology. Mean adrenal lengths were 14.12 ± 2.25 mm on the left and 14.33 ± 1.97 mm on the right. Cranial and caudal pole heights were 3.10 ± 0.44 and 3.26 ± 0.33 mm, respectively, on the left, and 3.19 ± 0.61 and 3.50 ± 0.52 mm, respectively, on the right. Within each gland, the caudal pole was significantly greater in height than the cranial pole. In addition, the right caudal pole height was significantly greater than the left (p = 0.002). No significant associations with sex or body weight were found. Corticomedullary boundaries were visible in 94.7% of left and 76.3% of right adrenal glands.ConclusionThis study provides species-specific ultrasonographic reference values for Korean raccoon dogs, supporting improved interpretation in clinical and conservation medicine.